2021
DOI: 10.1101/2021.04.13.439695
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in regional white matter volumetry and microstructure during the post-adolescence period: a cross-sectional study of a cohort of 1,713 university students

Abstract: Human brain white matter undergoes a protracted maturation that continues well into adulthood. Recent advances in diffusion-weighted imaging (DWI) methods allow detailed characterizations of the microstructural architecture of white matter, and they are increasingly utilised to study white matter changes during development and ageing. However, relatively little is known about the late maturational changes in the microstructural architecture of white matter during post-adolescence. Here we report on regional ch… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 108 publications
(204 reference statements)
0
2
0
Order By: Relevance
“…Lower FA in the right cingulum may be due to less myelination, or to less organized or less densely packed fibers. A recent, large study of young adults using multishell dMRI showed that the neuronal density of the left cingulum was greater than that of the right, while the orientation dispersion index was higher on the right, indicating less coherence in fiber direction (Tsuchida et al, 2021 ). Lower fiber density could mean greater elasticity and thus more stretch during impact; finite element modeling consistently indicates high axonal strain in the cingulum (Chatelin et al, 2011 ; Zhang & Gennarelli, 2011 ; Zhao et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lower FA in the right cingulum may be due to less myelination, or to less organized or less densely packed fibers. A recent, large study of young adults using multishell dMRI showed that the neuronal density of the left cingulum was greater than that of the right, while the orientation dispersion index was higher on the right, indicating less coherence in fiber direction (Tsuchida et al, 2021 ). Lower fiber density could mean greater elasticity and thus more stretch during impact; finite element modeling consistently indicates high axonal strain in the cingulum (Chatelin et al, 2011 ; Zhang & Gennarelli, 2011 ; Zhao et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A large study of young adults using multi-shell dMRI recently showed that the neuronal density of the left cingulum was greater than that of the right cingulum, while the orientation dispersion index (ODI; higher values indicate less coherence in fiber direction) was higher in the right cingulum. 52 Lower fiber density could mean greater elasticity and thus more stretch during impact; finite element modeling consistently indicates high axonal strain in the cingulum. [53][54][55] Some studies have found lower tract asymmetry in women than in men, 45,56 although such differences may be minor.…”
Section: Discussionmentioning
confidence: 99%